Educational scholarship on women: A feminist analysis of two decades of adult education literature - Peggy A. Sissel (Adult Education Research Conference, 1993)
Research on women and adult education (AE) remains at low levels, with little evidence of a feminist perspective guiding it. This two-part study explores the need to develop this body of knowledge.